Phosphorus‐containing Salen‐metal complexes investigated for enhancing the fire safety of thermoplastic polyurethane (TPU). (23rd January 2020) - Zhang, Yabin; Cui, Jinfeng; Wang, Lurong; Liu, He; Yang, Baoping; Guo, Junhong; Mu, Bo; Tian, Li
Abstract : Three novel phosphorus‐containing Salen‐based derivatives (Salen‐DPCP‐M: M = Ni, Zn, and Mn), which include both phenyl phosphate structures (DPCP) and Salen‐metal complexes, were prepared for enhancing the fire safety of thermoplastic polyurethane (TPU). Thermogravimetric analysis (TGA) showed that Salen‐DPCP‐M altered the thermal degradation pathways of TPU probably due to the phosphorus‐containing structure of Salen‐DPCP‐M. The cone calorimeter test showed that the addition of 3 wt% of Salen‐DPCP‐Ni, Salen‐DPCP‐Zn, and Salen‐DPCP‐Mn lowered the peak of heat release rate (PHRR) from 1495 kW/m 2 for neat TPU to 690, 875, and 813 kW/m 2, respectively, for the TPU composites, which demonstrated that Salen‐DPCP‐M improved the fire safety of TPU. In addition, the release of toxic CO gas from the Salen‐DPCP‐Ni/TPU and Salen‐DPCP‐Zn/TPU composites was reduced by 78.2% and 80.0%, respectively. The results of TGA/infrared spectrometry (TG‐FTIR) showed that the incorporation of Salen‐DPCP‐Ni promoted the release CO2, while reducing the formation of harmful gases. Laser Raman spectroscopy (LRS) and scanning electron microscopy (SEM) showed that Salen‐DPCP‐Ni/TPU and Salen‐DPCP‐Zn/TPU composites formed a dense and stable char layer. Herein, the mechanism of these flame retardants containing novel phosphorus‐containing Salen‐metal complexes is also proposed.